2021
DOI: 10.3803/enm.2021.1109
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Profile and Its Prognostic Impact on the Coronavirus Disease 2019 in Korean Patients

Abstract: Background: Data on the association between coronavirus disease 2019 (COVID-19) and thyroid have been reported, including overt thyrotoxicosis and suppression of thyroid function. We aimed to evaluate the thyroid hormone profile and its association with the prognosis of COVID-19 in Korean patients.Methods: The clinical data of 119 patients with COVID-19, admitted in the Myongji Hospital, Goyang, South Korea, were retrospectively evaluated. The thyroid hormone profiles were analyzed and compared based on diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
(70 reference statements)
4
28
0
Order By: Relevance
“…A study consisting of 50 patients demonstrated that a more severe COVID-19 maybe linked with a lower TSH (19). Subsequently, the clinical data of 119 patients showed that TSH levels were significantly lower in patients with severe to critical disease than in those with nonsevere disease (4). Moreover, what we know is that ESS is common in various acute and chronic conditions as a risk factor for the severity of diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study consisting of 50 patients demonstrated that a more severe COVID-19 maybe linked with a lower TSH (19). Subsequently, the clinical data of 119 patients showed that TSH levels were significantly lower in patients with severe to critical disease than in those with nonsevere disease (4). Moreover, what we know is that ESS is common in various acute and chronic conditions as a risk factor for the severity of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to find biomarkers of disease severity and death to identify earlier, intervene effectively, and save lives ultimately. Previous studies suggested that changes in thyroid function relevant parameters have been thought to be significant in COVID-19 patients (3)(4)(5). However, the effects of COVID-19 on the thyroid axis and the crosstalk between the thyroid axis and inflammation/coagulopathy/fibrinolysis during the SARS-CoV-2 infection remain not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the HPA axis, there is also evidence that suggests reduced activity of the hypothalamic pituitary thyroid axis. The levels of total triiodothyronine (T3) and thyroid stimulating hormone (TSH) are lower in COVID-19 patients ( 78 , 79 ). It was also reported that within the group of COVID-19 cases, 61.9% (52/84) patients presented with thyroid function abnormalities and the proportion of thyroid dysfunction was higher in severe cases than mild/moderate cases.…”
Section: Covid-19 and Endocrine Activitymentioning
confidence: 99%
“…[ 18 ] Approximately 15% of adults with COVID-19 infection have abnormal thyroid function, and circulating triiodothyronine levels are associated with adverse COVID-19 outcomes. [ 19 , 20 ] Therefore, physicians should be aware of the possibility of thyroid dysfunction in patients with COVID-19. In the present case, his condition was stable following treatment with amiodarone, and levothyroxine replacement.…”
Section: Discussionmentioning
confidence: 99%